Perkembangan Spasial Kota-Kota Kecil Di Jawa Tengah - Nanda Adi Prawatya (Jurnal Wilayah dan Lingkungan, 2013)
The level of urbanization in Central Java province is increased by looking at the changes occurred in the vast agricultural land use that has declined, especially in a small town. In the past 10 years, built-up land use in Central Java has increased by 70.1%. In addition, also in the past 10 years the road network has increased by 0.43%. This happened because the capacity of urbanization and activities movement in a large city is increasing and can not accommodate at one point, so that other areas are required for equalization purpose. This raises several questions, such as what the determining factors of urban space are and how the spatial development of small towns in Central Java is. The purpose of this study was to determine the typology of small towns in Central Java based on aspects of the space structure, land use and infrastructure. Small towns are concentric structured with slow land development because there is only a single activity center. The potential of the area is a rural urban area with its center activity only from the agricultural sector. Multiple nuclei structured small towns are quite developed between moderate to high level. This is due to the existence of several centers within the small towns that resulted in high development of built-up land. Based on spatial typology pattern of small towns, it can be explained that the small towns located on the outskirts of major cities such as Surakarta, Yogyakarta, Semarang, Tegal, Magelang, Salatiga, and Pekalongan, have a dependency to those main city. Thus, city development is not only influenced by urbanization, but also other factors such nature comparative advantages (topography, natural resource, historical) and human-made physic (infrastructure network, social facilities).